Effect on hydrophobicity and antimicrobial behavior of epoxy resin due to silane functionalized TiO2 as nanofillers. Issue 8 (17th November 2021) - Nisha, P.; Suresh, S.; Saravanan, P.; Jayamoorthy, K.; Subash, B.; Prakash, S. M.; Rajagopalan, N. R.; Ravichandran, C.
Abstract: 4-Aminobutyltriethoxysilane functionalized TiO2 nanoparticles (TiO2 -ABTES) dispersed diglycidyl ethers of bisphenol-A (DGEBA-GY260) were studied for antimicrobial applications. Epoxy nano-hybrid coatings of four different concentrations (1, 3, 5 and 7 wt %) were developed using TiO2 -ABTES as the dispersed phase and a commercially available DGEBA as the matrix phase. Triethylenetetramine (TETA) used to cure the nanocomposites films. The structural characteristics of these materials were investigated by Fourier transform infrared spectral studies, Scanning electron microscopy and atomic force microscope analysis. The surface characteristics of the samples were estimated from contact angle measurements and calculated surface free energy and adhesion energy. The bacteriological tests were done using the agar diffusion method with different concentrations of TiO2 -ABTES. The antimicrobial activity test noted that the antimicrobial activity of 7 wt% TiO2 -ABTES nanoparticles loaded epoxy nanocomposite film has a better inhibition zone against all pathogens under study.